2015
DOI: 10.1155/2015/584189
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Betulin as a Potent Anticancer Agent

Abstract: Numerous plant-derived substances, and their derivatives, are effective antitumour and chemopreventive agents. Yet, there are also a plethora of tumour types that do not respond, or become resistant, to these natural substances. This requires the discovery of new active compounds. Betulin (BE) is a pentacyclic triterpene and secondary metabolite of plants abundantly found in the outer bark of the birch tree Betulaceae sp. BE displays a broad spectrum of biological and pharmacological properties, among which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 79 publications
(169 reference statements)
2
88
0
1
Order By: Relevance
“…Numerous anticancer strategies are based on inhibition of cell proliferation and promotion of cell death [12]. Natural compounds derived from plants are frequently used as potential anticancer substances [13, 14]; these compounds are easily available because of their common occurrence in nature. Our results obtained from proliferation assay indicated that the highest cytotoxicity in metastatic Me-45 melanoma cells was obtained after 72 h incubation with new betulin derivatives containing lysine and ornithine (IC 50  = 2.456 μM; IC 50  = 2.465 μM, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous anticancer strategies are based on inhibition of cell proliferation and promotion of cell death [12]. Natural compounds derived from plants are frequently used as potential anticancer substances [13, 14]; these compounds are easily available because of their common occurrence in nature. Our results obtained from proliferation assay indicated that the highest cytotoxicity in metastatic Me-45 melanoma cells was obtained after 72 h incubation with new betulin derivatives containing lysine and ornithine (IC 50  = 2.456 μM; IC 50  = 2.465 μM, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Reviews on anticancer properties of betulinic acid (5) and its derivatives have been provided [25][26][27][28][29][30]. A review on the anticancer and chemopreventive potential of betulin (4) in vitro and in vivo has also been provided [31].…”
Section: Resultsmentioning
confidence: 99%
“…Fatostatin, a chemical SREBP inhibitor, has been found to suppress prostate cancer cell proliferation and reduce tumor growth 50. In addition, the natural compound betulin, which inhibits SREBP activation, has been shown to have broad spectrum of anticancer activity in vitro and in vivo 51. Inhibition of ACS by Triacscin C significantly induces apoptosis in p53-defective human cancer cells and suppresses growth of xenograft tumors 52…”
Section: Anticancer Agents Targeting Lipid Metabolic Reprogrammingmentioning
confidence: 99%